1984
DOI: 10.1016/0014-5793(84)80054-x
|View full text |Cite
|
Sign up to set email alerts
|

A structural comparison of guinea pig thyroid and fat TSH receptors by photoaffinity labelling

Abstract: TSH receptors from guinea pig thyroid and epididymal fat have been covalently crosslinked to 125I‐labelled TSH conjugated to N‐hydroxysuccinimidyl‐4‐azidobenzoate. Analysis by SDS—PAGE and autoradiography showed bands corresponding to TSH subunits (M r 14 000) and intact TSH (M r 28 000; subunits crosslinked) and two at higher M r separated by 14 000. The latter bands represented one or two subunits of TSH crosslinked to a subunit of the TSH receptor with M r 57 000 (fat) or 60 000 (thyroid). These M r values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Posttranslational proteolysis clips the TSH receptor (TSHR) into two subunits (referred to as α, or A, and β, or B) (15,16), linked to each other by disulfide bonds. These α and β subunits are formed by intramolecular cleavage, apparently at multiple sites, with removal of an intervening polypeptide segment of approximately 50 amino acids (amino acids 317-367) (17,18).…”
Section: Tshr Signal Transduction Regulation and Maturationmentioning
confidence: 99%
“…Posttranslational proteolysis clips the TSH receptor (TSHR) into two subunits (referred to as α, or A, and β, or B) (15,16), linked to each other by disulfide bonds. These α and β subunits are formed by intramolecular cleavage, apparently at multiple sites, with removal of an intervening polypeptide segment of approximately 50 amino acids (amino acids 317-367) (17,18).…”
Section: Tshr Signal Transduction Regulation and Maturationmentioning
confidence: 99%
“…In the case of the TSH receptor, we have found TSH coupled to photoactive cross-linking reagents to be particularly useful (98)(99)(100)(101)(102)(103)(104)(105)(106). These studies have indicated that both subunits of TSH form part of the hormone's receptor binding site (101,102).…”
Section: A Photoaffinity Labelingmentioning
confidence: 99%
“…Photoaffinity labeling studies suggest that the TSH receptor has only one binding site for TSH (98)(99)(100)(101)(102)(103)(104)(105)(106)110) and presumably therefore only one binding site for TRAb. These conclusions are confirmed by the immunoprecipitation and gel filtration studies which were 116 REES SMITH ET AL.…”
Section: Valency Of the Tsh Receptor For Tsh And Trabmentioning
confidence: 99%
“…Sequence analysis indicates that the TSHR gene codes for a single peptide chain with a computed molecular mass of 84 kDa (Libert et al 1989, Nagayama et al 1989, Frazier et al 1990, Misrahi et al 1990. However the region of the peptide chain linking the receptor's large extracellular domain to its seven membrane spanning domain is readily cleaved giving rise to an A subunit (extracellular domain) linked by a disulphide bridge(s) to a B subunit (membrane spanning domain) (Buckland & Rees Smith 1984, Kajita et al 1985a,b, Rees Smith et al 1988, Loosfelt et al 1992.…”
Section: Introductionmentioning
confidence: 99%